The Influence of Competence and Work Discipline on Employee Performance: The Mediating Role of Work Motivation: at the General and Administrative Bureau of the Papua Provincial Leadership - Jamroni; Kambuaya, Balthasar; Wambrauw, Oscar O. (Adhigana Papua: Jurnal Ilmiah Magister Manajemen, 2025)
This study aims to examine the influence of competence and work discipline on employee performance at the Bureau of General Affairs and Leadership Administration of Papua Province, with work motivation as a mediating variable. Using a quantitative approach with a saturated sample of 93 employees, data were collected through a structured questionnaire and analyzed using multiple regression, path analysis, and Sobel test. The results show that both competence and work discipline directly affect employee performance. However, only work discipline has a significant effect on work motivation. Furthermore, work motivation significantly mediates the relationship between work discipline and performance, but not between competence and performance. These findings highlight that employee performance is strongly influenced by discipline and motivation, suggesting that efforts to enhance performance should prioritize motivational strategies and discipline reinforcement rather than relying solely on competency development. The study contributes to public management literature by proposing an integrated model that clarifies the role of psychological factors in shaping bureaucratic performance in a special autonomy region. Implications for human resource policy and future research directions are also discussed.